2012
DOI: 10.1159/000336129
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Fluoroquinolone-Resistant <i>Escherichia coli</i> O25:H4-ST131 (CTX-M-15-Nonproducing) Strains Isolated in Japan

Abstract: Background: Fluoroquinolone-resistant and extended-spectrum β-lactamase (ESBL)-carrying multidrug-resistant Escherichia coli have become severely problematic. In particular, a lineage of multilocus sequence-type ST131 which belongs to O25:H4 and carries ESBL CTX-M-15 has spread worldwide. Methods: Fluoroquinolone-resistant E. coli strains were isolated from various clinical specimens in a commercial clinical laboratory in 2008 and 2009 in Hokkaido Prefecture, Japan. Results: Among 478 clinical isolates, 112 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 44 publications
(30 reference statements)
1
30
0
Order By: Relevance
“…One of the most prominent characteristics of ST131 is its fluoroquinolone resistance, to which this clonal group is the major contributor worldwide (9,(42)(43)(44)(45)(46)(47). We have recently demonstrated that this phenotype is predominantly associated with strains carrying an NA114-like fimH30 allele (48).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most prominent characteristics of ST131 is its fluoroquinolone resistance, to which this clonal group is the major contributor worldwide (9,(42)(43)(44)(45)(46)(47). We have recently demonstrated that this phenotype is predominantly associated with strains carrying an NA114-like fimH30 allele (48).…”
Section: Discussionmentioning
confidence: 99%
“…First, we showed that several strains of certain populations of fluoroquinolone-resistant E. coli, including major extraintestinal pathogenic lineages O25b:H4-ST131-H30R and O1-ST648, show reduced susceptibility to TGC (1.0% and 3.6% of fluoroquinolone-resistant E. coli isolates were resistant or nonsusceptible to TGC, respectively). Considering the frequency of fluoroquinolone resistance (for example, the fluoroquinolone resistance rate in E. coli was 23.4% in our previous study [4]), approximately 0.8% or fewer of E. coli clinical isolates could be nonsusceptible or resistant to TGC. Indeed, previous large-scale surveillance studies indicated that fewer than 0.3% of the E. coli clinical isolates were nonsusceptible to TGC (10, 11).…”
mentioning
confidence: 83%
“…Two hundred seventy-seven fluoroquinolone-susceptible E. coli isolates (ciprofloxacin [CIP] MIC, Ͻ0.125 mg/liter) and 194 fluoroquinolone-resistant E. coli isolates (CIP MIC, Ͼ2 mg/liter) were isolated from human clinical specimens. Of these, 100 fluoroquinolone-susceptible E. coli isolates and 118 fluoroquinolone-resistant E. coli isolates (six strains were added for this study) were from human specimens collected in 2008 and 2009, as described previously (4). One hundred seventy-seven fluoroquinolone-susceptible E. coli isolates and 76 fluoroquinolone-resistant E. coli isolates were from human clinical specimens collected in 2015 and 2016 in Japan (Sapporo Medical University Hospital, Sapporo, Japan) and stored in the laboratory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This lineage is FQ resistant and often acquires ESBL genes, particularly the CTX-M-15 of group 1. In contrast, other ESBL genes, particularly CTX-M groups 9 (CTX-M-14 and 27) and 2 (CTX-M-2), are dominant in Japanese O25b:H4-ST131 strains [14,15]. However, CTX-M-15-producing O25b:H4-ST131 strains have been found in recent years in Japan [16].…”
Section: Introductionmentioning
confidence: 99%